2002
DOI: 10.1073/pnas.062053399
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of bone formation and prevention of bone loss by prostaglandin E EP4 receptor activation

Abstract: Bone remodeling, comprising resorption of existing bone and de novo bone formation, is required for the maintenance of a constant bone mass. Prostaglandin (PG)E 2 promotes both bone resorption and bone formation. By infusing PGE 2 to mice lacking each of four PGE receptor (EP) subtypes, we have identified EP4 as the receptor that mediates bone formation in response to this agent. Consistently, bone formation was induced in wild-type mice by infusion of an EP4-selective agonist and not agonists specific for oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
260
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(275 citation statements)
references
References 24 publications
9
260
4
2
Order By: Relevance
“…In the bone marrow cell cultures, mineralised nodule formation was absent and could not be increased by treatment with PGE 2 [25]. When PGE 2 was infused onto the periosteal surfaces of femurs, it caused local bone formation in the wild type but not in EP4 KO mice [26]. The lack of skeletal phenotype in the adult EP4 KO mice suggests that EP4 receptor is not essential for the bone growth and maturation in mice [17].…”
Section: Bone Phenotype Of Mice Lacking Ep Receptorsmentioning
confidence: 99%
“…In the bone marrow cell cultures, mineralised nodule formation was absent and could not be increased by treatment with PGE 2 [25]. When PGE 2 was infused onto the periosteal surfaces of femurs, it caused local bone formation in the wild type but not in EP4 KO mice [26]. The lack of skeletal phenotype in the adult EP4 KO mice suggests that EP4 receptor is not essential for the bone growth and maturation in mice [17].…”
Section: Bone Phenotype Of Mice Lacking Ep Receptorsmentioning
confidence: 99%
“…Signaling through the BMP 21, PGE2 22, or Wnt receptors 23 eventually results in the stimulation of Runx2 expression, an early marker of osteoblast differentiation. It was recently demonstrated that rapamycin, which is an inhibitor of the mammalian target of rapamycin complex 1 (mTORC1), a serine/threonine kinase, inhibited osteoblast differentiation through the reduction of Runx2 expression in an osteoblast cell line and bone marrow‐derived stromal cells 24.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E 2 (PGE 2 ) is an anabolic nonpeptide reagent that has been implicated as having a role in bone formation (5)(6)(7)(8)(9). However, PGE 2 causes severe side effects systemically, and 3 daily injections of PGE 2 for several weeks are required to stimulate bone formation (9).…”
mentioning
confidence: 99%
“…However, PGE 2 causes severe side effects systemically, and 3 daily injections of PGE 2 for several weeks are required to stimulate bone formation (9). The anabolic action of PGE 2 in target cells is mediated by G protein-coupled receptor subtypes, including EP1, EP2, EP3, and EP4.…”
mentioning
confidence: 99%
See 1 more Smart Citation